2014
DOI: 10.1590/s1806-83242014.50000005
|View full text |Cite
|
Sign up to set email alerts
|

Immediate and delayed photoactivation of self-adhesive resin cements and retention of glass-fiber posts

Abstract: The aim of this study was to evaluate the effect of immediate and delayed photoactivation of self-adhesive resin cements (SARCs) on the retention of glass-fiber posts luted into root canals. Bovine incisors were endodontically treated, and post holes of 9 mm in depth were prepared. Fiber posts were luted using one of two SARCs, BisCem  (Bisco Inc., Schaumburg, USA) or RelyX Unicem clicker (3M ESPE, Saint Paul, USA), or a regular (etch-and-rinse) resin cement (AllCem; FGM, Joinvile, Brazil). Photoactivation wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 22 publications
1
12
0
2
Order By: Relevance
“…The polymerization shrinkage of these materials may exceed their bond strength, resulting in gaps forming at the dentin-resin cement interface, loss of retention and the displacement of the posts 4 . This may be caused by the stress that results from the polymerization shrinkage generated in the root canal by the composition of resin cements and different light curing techniques 10 , 23 .…”
Section: Introductionmentioning
confidence: 99%
“…The polymerization shrinkage of these materials may exceed their bond strength, resulting in gaps forming at the dentin-resin cement interface, loss of retention and the displacement of the posts 4 . This may be caused by the stress that results from the polymerization shrinkage generated in the root canal by the composition of resin cements and different light curing techniques 10 , 23 .…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that a delay time of 3 or 5 minutes prior to light-activation of dual-cured cements can reduce the shrinkage stress and improve the bond strength 7 without significantly altering the mechanical properties. 13,69,71 A delay in light activation of dual curing resin cement for cementing ceramic inlays reduced the post-gel shrinkage and decreased the shrinkage stresses at the pulpal floor, which may reduce post-operative sensitivity. 11 …”
Section: Use Of Bulk Fill Compositementioning
confidence: 99%
“…These deleterious effects mainly occur when post sectioning is performed immediately after post cementation. Since cement setting is mainly activated by chemical initiation during the post cementation (7), the resin cements usually exhibit a low degree of conversion immediately after the cementation and thus reduce the bond strength to dentin (8). In contrast, when post sectioning is performed after the core build-up, the resin cement exhibits an increased degree of conversion.…”
Section: Introductionmentioning
confidence: 99%